Marcos foreign policy - Domingo, Benjamin B. (Marcos Presidential Center, 2007)
This book is about the foreign policy of President Marcos. One might take issue that foreign policy is only about dealing with other nations. On the other hand, President Marcos, as a student of world politics, understood clearly that foreign policy is only an axtension of domestic policy and that foreign policy without regard to national interest is baseless.